2015
DOI: 10.17795/zjrms962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin on RAC1 Gene Expression as a Marker of Metastasis in Cervical Cancer Cells

Abstract: Background: Cancer metastasis is the most important cause of cancer death and different treatment strategies have targeted on preventing the occurrence of metastasis. Quercetin is a flavonoid and widely used as an antioxidant and recent studies have discovered its anticancer and antiproliferative capabilities. Rac1 is protein known to involve in tumor invasion and metastases. Objectives: In this study, we investigated the effect of quercetin on expression of Rac1 protein. Materials and Methods:In this experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A study showed that Rac1 plays an important role in the regulation of apoptosis in cervical cancer cells, and its reduction can potentially increase chemosensitivity to cisplatin [147]. Under experimental conditions on HeLa cells, the authors found that a phytochemical quercetin decreased Rac1 expression, which could be useful in reduction of cervical cancer metastasis [148]. Similarly, the effect of anti-cancer phytochemical rocaglamide-A inhibited the activity of RhoA, Rac1, and Cdc42 GTPases and suppressed metastasis formation [149].…”
Section: Cervical Cancermentioning
confidence: 99%
“…A study showed that Rac1 plays an important role in the regulation of apoptosis in cervical cancer cells, and its reduction can potentially increase chemosensitivity to cisplatin [147]. Under experimental conditions on HeLa cells, the authors found that a phytochemical quercetin decreased Rac1 expression, which could be useful in reduction of cervical cancer metastasis [148]. Similarly, the effect of anti-cancer phytochemical rocaglamide-A inhibited the activity of RhoA, Rac1, and Cdc42 GTPases and suppressed metastasis formation [149].…”
Section: Cervical Cancermentioning
confidence: 99%